Differential Effects of Unihemispheric Concurrent Dual-Site and Conventional tDCS on Motor Learning: A Randomized, Sham-Controlled Study - Ailin Talimkhani (Basic and Clinical Neuroscience, 2019)
Introduction: Based on the literature, unihemispheric concurrent dual-site anodal transcranial Direct Current Stimulation (a-tDCSUHCDS) of primary Motor cortex (M1) and Dorsolateral Prefrontal Cortex (DLPFC) would be more efficient than conventional a-tDCS of M1 to induce larger and longer-lasting M1 corticospinal excitability. The main objective of the present study was to compare the effects of a-tDCSUHCDS and conventional M1 a-tDCS on the extent and durability of the motor sequence acquisition in healthy individuals. Methods: In this randomized sham-controlled study, healthy volunteers were randomly divided into three groups: experimental (a-tDCSUHCDS), control (M1 a-tDCS), and sham stimulation groups. The participants practiced serial response time task over three consecutive days when they simultaneously received a-tDCS. Using the skill measure, we assessed motor learning up to 4 weeks after the completion of experimental conditions. Results: Data analysis revealed that all groups exhibited the improved trend over the training course (P<0.001). There were no significant differences in skill acquisition among groups at post-intervention (P>0.05), while a significant improvement was observed between experimental and sham group at the retention time (P<0.05). Moreover, there were no significant differences between the control and two other groups with regard to the retention time (P>0.05). Conclusion: These results revealed a significant increase in the skill acquisition by a-tDCSUHCDS technique with regard to retention issue, which could be a valuable finding in neuro-rehabilitation field.